Strengthening Character Discipline Through Religious Extracurricular Activities at MI Unggulan Jabalul Khoir - Awang Sulistiyawan; Fitri Puji Rahmawati (Contemporary Education and Community Engagement (CECE), 2026)
This study aims to describe the reinforcement of discipline character through religious extracurricular activities at MI Unggulan Jabalul Khoir. The research employed a qualitative descriptive method by directly observing the implementation of religious extracurricular programs and their role in shaping students’ discipline. Data were collected through interviews with the school principal, extracurricular mentors, and 13 student participants. The analysis was conducted using Miles and Huberman’s interactive model, which involves four stages: extensive data collection, data reduction based on the research focus, data presentation, and drawing conclusions. Data validation was carried out using theoretical and source triangulation. The study found three main religious extracurricular activities: Hadrah (disciplining through art), Karate (disciplining through physical training), and Tadzkir (a more in-depth spiritual character-building program led by a religious teacher with deeper expertise). Tadzkir was integrated across all extracurricular activities and focused on leadership training, daily reflection, talent expression, and planning for the future. The program proved effective, as demonstrated by three students winning in Fahmil Qur'an and Hadrah competitions